2016
DOI: 10.1186/s13014-016-0604-z
|View full text |Cite
|
Sign up to set email alerts
|

Local efficacy and survival outcome of salvage endoscopic therapy for local recurrent lesions after definitive chemoradiotherapy for esophageal cancer

Abstract: BackgroundSalvage endoscopic therapy (SET), such as endoscopic mucosal resection (EMR) and photodynamic therapy (PDT), is a less-invasive treatment for local failure at the primary site after chemoradiotherapy (CRT) for esophageal squamous cell carcinoma (ESCC). We conducted this retrospective study to clarify the risk factors for local recurrence along with the long term results after SET for recurrent lesions after definitive CRT for ESCC.MethodsWe enrolled 77 consecutive patients who underwent EMR or PDT fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Thus, due to unexpected outcomes, controversy exists regarding salvage therapy. There are few reports on endoscopic submucosal dissection (ESD) 10 11 12 despite many reports describing endoscopic mucosal resection (EMR) 13 14 15 . Locoregional failure or a metachronous lesion after CRT may be accompanied by tissue fibrosis 10 11 16 , which may cause difficulty in performing ESD and may lead to accidental perforation or massive bleeding during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to unexpected outcomes, controversy exists regarding salvage therapy. There are few reports on endoscopic submucosal dissection (ESD) 10 11 12 despite many reports describing endoscopic mucosal resection (EMR) 13 14 15 . Locoregional failure or a metachronous lesion after CRT may be accompanied by tissue fibrosis 10 11 16 , which may cause difficulty in performing ESD and may lead to accidental perforation or massive bleeding during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is clear that the elderly may suffer greater toxicities with adjuvant therapy, and clinical hesitation may hence give way to a "watchful waiting" approach to treat only if recurrent disease develops. As such, there are several reports delineating the safety and efficacy of salvage therapies following local/locoregional recurrences of EC, although predictably the cT1-2N0 cohort is underrepresented [20][21][22]. Second, similar to other thoracic neoplasms [23], there are data showing that the presence of limited/minimal nodal involvement on complete nodal dissection may provide satisfactory outcomes in cT1-2N0 disease, without specific necessity to perform routine adjuvant therapy [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In case series from Japan, salvage endoscopic resection of residual cancer after definitive CRT has been reported in esophageal squamous cell carcinoma 3 4 5 . Yano et al reported a local failure rate of 34 % in patients treated with definitive CRT after diagnosis of squamous cell carcinoma of the esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…Yano et al reported a local failure rate of 34 % in patients treated with definitive CRT after diagnosis of squamous cell carcinoma of the esophagus. Because of the high local recurrence rate for squamous cell carcinomas, curative local control is crucial and salvage endoscopic resection provides a therapeutic option with curative intent 3 5 . Reports of curative treatment with salvage endoscopic resection of recurrent or residual squamous cell carcinoma after definitive CRT have been described, however to date, curative treatment with salvage endoscopic resection in cases of residual adenocarcinoma after CRT has not been reported.…”
Section: Introductionmentioning
confidence: 99%